PENGEMBANGAN MEDIA ROBALMEONCA (ROLLING BALL AND QUESTION CARD) PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Pertiwi, Bunga Arum Bella; Lian, Bukman; Aryaningrum, Kiki (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop a valid and practical media, specifically a rolling ball and question card, for the subject of Pancasila Education in the fourth grade of elementary school. The research type used is Research & Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were the fourth-grade students at SD Negeri 34 Palembang. The validity test results showed an average of 83.52% from subject matter experts, 87.64% from language experts, and 91.26% from media experts, all falling under the